“Mitigating the evils that the revolution in the Peninsula had caused in America”: The absolutist governments and overseas provinces in 1823 - Rodríguez Tapia, Andrea (Hispania Nova, 2022)
This paper analyzes the measures taken by the Regency and the absolutist government established in Spain in 1823 with respect to the American territories. It studies the administrative and governmental dispositions executed by the Regency and the Council of the Indies, as well as the government ministers, particularly the actions of Víctor Damián Sáez. This work seeks to contribute to the understanding of the second absolutist restoration of Ferdinand VII and to the study of the American policy developed by that government to face the loss of continental America.
Keywords: Ferdinand VII; restoration of absolutism; Council of the Indies; Víctor Damián Sáez; overseas territoires; loss of America